SCHEDULED BASED CLOUD RESOURCE ALLOCATION - Hendy Mizuardy (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2017)
The objective of this research The tremendous implementation of cloud computing technology has become a new trend that users can easily utilize high resources through IaaS platform. IaaS is more economical and easier way to have physical resources; in this case Virtual Machines in the cloud, rather than building the infrastructure by their own. To deliver internet services to users such as website, email service or other software applications, a service provider can utilize IaaS platform by leasing virtual infrastructure from a cloud provider and deploy their services on that VMs. However, it becomes a challenge for a service provider to maintain their services due to the increasing number of user requests. They have to maintain resources availability to provide maximum performance to meet their user satisfaction with optimal resources utilization. The approach in this paper will solve this problem by providing service provider a resource monitor module. The module monitors VMs workload based on schedule approach; peak time and off-peak time. According to these two criteria, the service provider can predict and allocate sufficient resources.